Evaluation of two different applications for cellulose isolated from sugarcane bagasse in a biorefinery concept - Candido, R. G.; Gonçalves, A. R. [UNESP] (Elsevier, 2019)
The present work aimed at investigating the isolation and application of cellulose from sugarcane bagasse in two different processes according to the biorefinery concept. The cellulose isolation step involved, in the following order, an H2SO4 (10% v/v) treatment, an NaOH (5% w/v) treatment, and a chemical bleaching with H2O2 (5% v/v). The isolated cellulose was characterized to determine its chemical composition and physical structure. The bleached cellulose was used for the synthesis of carboxymethylcellulose (CMC), and the materials obtained after acid and alkaline treatments were applied in the process of enzymatic hydrolysis. CMC degree of substitution was 0.59, evidencing that it is soluble in water. The enzymatic conversion of cellulose achieved 73.35% and the content of lignin was demonstrated to interfere directly in the efficiency of the enzymes. The results showed that cellulose from sugarcane bagasse can be successfully applied in the two investigated technological processes.
Keywords: Biorefinery; Carboxymethylcellulose; Cellulose; Enzymatic hydrolysis; Sugarcane bagasse